Small bound isomorphisms of the domain of a closed ∗-derivation - Toshiko Matsumoto; Seiji Watanabe (International Journal of Mathematics and Mathematical Sciences)
The domain 𝒟(δ) of a closed ∗-derivation δ in C(K) (K: a compact Hausdorff space) is a generalization of the space C(1)[0,1] of differentiable functions on [0,1]. In this paper, a problem proposed by Jarosz (1985) is studied in the context of derivations instead of C(1)[0,1].